Fixed-Time Prescribed Performance Path-Following Control for Autonomous Vehicle With Complete Unknown Parameters - Liang, Zhongchao; Wang, Zhongnan; Zhao, Jing; Wong, Pak Kin; Yang, Zhixin; Ding, Zhentao (IEEE transactions on industrial electronics (1982), 2023)
This paper investigates the issue of fixed-time path-following control for autonomous ground vehicles (AGVs) with completely unknown parameters subject to preset error constraints. Before converging the path-following errors, a fixed-time prescribed performance control (PPC) protocol is developed to guarantee the selected nonsingular sliding manifold evolving within the preset boundaries. Then, the fixed-time PPC target for the preview error of the AGV can be achieved by satisfying the parameter inequality. Furthermore, the designed adaptive laws can ensure the control accuracy without knowledge of vehicle parameters. Finally, the hardware-in-the-loop (HIL) tests of multiple maneuvering conditions demonstrate that the proposed fixed-time PPC protocol can provide superior comprehensive path-following performance for the AGV over the conventional fixed-time controller, and the preview error can never violate the prescribed performance constraints.